San Tiago Dantas: ideias e rumos para a Revolução Brasileira (1929-1964) - Ribeiro, Renato Ferreira (2021)
Francisco Clementino de San Tiago Dantas (1911-1964) was a jurist, politician and intellectual from Rio de Janeiro who played an important role in Brazilian public life between 1929 and 1964. His intellectual production and political action are deeply connected to the construction of the centralized national State in Brazil and to the country’s transition from agrarian to urban, industrial society. Similar to several other intellectuals of his generation, San Tiago Dantas began his trajectory linked to the Brazilian Integralist Action (a fascist inspired movement), converting to the democratic and developmental field after World War II and becoming a leader and an ideologist of the Brazilian Labor Party in the 1950s and 1960s. The objective of this thesis is to investigate Dantas social trajectory - highlighting his networks of relationships and attachment to groups - and his intellectual production - seeking to map his theoretical and political-ideological formulations - in the period from 1929 to 1964. In the research, I used published and unpublished texts by the author (books, speeches, manuscripts, interviews, transcripts of classes and courses), correspondence sent and received, memories and interviews of contemporary characters and newspaper and magazine reports. The analysis of this material allowed the identification of three political-ideological phases in the trajectory of San Tiago Dantas, described in this thesis: 1) catholic/ integralist (1929-1945); 2) non-nationalist developmentalist (1945-1955); 3) laborist/reformist developmentalist (1955-1964).